3D-Printed Biocomposites from Hemp Fibers Reinforced Polylactic Acid: Thermal, Morphology, and Mechanical Performance - Esra Celik; Mesut Uysal; Omer Yunus Gumus; Cagatay Tasdemir (BioResources, 2024)
Thermal, morphological, and mechanical properties were studied for 3D-printed biocomposites prepared from polylactic acid (PLA) and hemp fibers. For this purpose, the neat PLA, PLA/Hemp fiber (3 wt%), PLA/Hemp fiber/Maleic anhydride (3 wt% and 0.6 wt%), and PLA/Hemp fiber/Maleic anhydride/Glycerol (3 wt% and 0.6 wt% + Glycerol added in 10% of PLA) biocomposites were extruded to obtain filaments for fused filament fabrication (FFF). Thermogravimetric analysis (TGA) provided temperatures corresponding to 5%, 10%, and 90% mass losses for materials before and after 3D printing. During 3D printing, filaments were extruded with a nozzle temperature of 220 ºC; consequently, their thermal properties worsened after 3D printing. In thermal analysis, Tg increased by adding hemp fiber and maleic anhydride but was decreased with glycerol addition. The tensile and flexural strengths of neat PLA and biocomposites were not statically different, but flexural strength was slightly increased by adding ingredients one by one. Regarding modulus of elasticity (MOE) of materials, the sample group of the PLA/hemp fiber/maleic anhydride had the highest value. However, glycerol addition decreased MOE by 17%. These results showed that material performance of the PLA could be improved or remain statistically identical by adding hemp fiber, maleic anhydride, and glycerol.